Plasmonic Chiral Metasurface Absorber Based on Bilayer Fourfold Twisted Semicircle Nanostructure at Optical Frequency - Yongzhi Cheng; Fu Chen; Hui Luo (Nanoscale Research Letters, 2021)
Abstract In this paper, we present a plasmonic chiral metasurface absorber (CMSA), which can achieve high selective absorption for right-handed and left-handed circular polarization (RCP, “+”, and LCP, “−”) lights at optical frequency. The CMSA is composed of a dielectric substrate sandwiched with bi-layer fourfold twisted semicircle metal nanostructure. The proposed CMSA has a strong selective absorption band, where absorption peaks for LCP and RCP lights occur at different resonance frequencies, reflecting the existence of a significant circular dichroism (CD) effect. It is shown that the absorbance of the CMSA can reach to 93.2% for LCP light and 91.6% for RCP light, and the maximum CD magnitude is up to 0.85 and 0.91 around 288.5 THz and 404 THz, respectively. The mechanism of the strong chiroptical response of the CMSA is illustrated by electric fields distributions of the unit-cell nanostructure. Furthermore, the influence of the geometry of the proposed CMSA on the circular polarization selective absorption characterization is studied systematically.